Space, Stars and Slimy Aliens - Arnold, Nick (Horrible Science, 2008)
If you think you can stomach the sick side of science, read on as we dig up the dirt on the world of plants. Find out when a fruit is really a vegetable, how plants keep us from suffocating and what stops trees from falling over. The book includes fact files, quirky quizzes and teacher tests.